Hadith #2301 - Sunan Abi Dawud - Abdullah bin al-Jrah عبد الله بن الجراح; Abdullah bin Bakr عبد الله بن بكر بن حبيب السهمي; Hafsa bint Umar; Hisham bin 'Urwa هشام بن عروة; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي; Ibrahim bin Tahman إبراهيم بن طهمان; Umm Atiyyah Ansariyah; Y'aqub bin Ibrahim bin Kathir يعقوب بن إبراهيم بن كثير بن زيد الدورقي; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Sunan Abi Dawud)
Ibn ‘Abbas said “The following verse abrogated the rule of passing her waiting period with her people. A year’s maintenance and residence. She may pass her waiting period now anywhere she wishes. ‘Ata said “If she wishes she can pass her waiting period with the people of her husband and live in the house left by her husband by will. Or she may shift if she wishes according to the pronouncement of Allah the Exalted. But if they leave (the residence) there is no blame on you for what th
Grade: Sahih

Hadith #2302 - Sunan Abi Dawud - Hafsa bint Umar; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Umm Atiyyah Ansariyah; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
‘Umm Athiyah reported the Prophet(ﷺ) as saying “A woman must not observe mourning for more than three (days) except for four months and ten days in the case of a husband and she must not wear a dyed garment except one of the types made of dyed yarn or apply collyrium or touch perfume except for a little costus or azfar when she has been purified after her menstrual courses. The narrator Ya’qub mentioned the words “except washed clothes” instead of the words “one of the types made o
Grade: Sahih

Hadith #3126 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Ayoub al-Sakhtiyani أيوب السختياني; Hafsa bint Sirin حفصة بنت سيرين; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: A child was born to me at night and I named him Ibrahim after his. He then narrated the rest of the tradition. Anas said: I saw it at the point of the death before the Messenger of Allah (ﷺ). Tears began to fall from the eyes of the Messenger of Allah (ﷺ). He said: The eye weeps and the heart grieves, but we say only what our Lord is pleased with, and we are grieved for you, Ibrahim.
Grade: Sahih

Hadith #3141 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibn Sirin محمد بن سيرين الأنصاري; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
By Allah, we did not know whether we should take off the clothes of the Messenger of Allah (ﷺ) as we took off the clothes of our dead, or wash him while his clothes were on him. When they (the people) differed among themselves, Allah cast slumber over them until every one of them had put his chin on his chest. Then a speaker spoke from a side of the house, and they did not know who he was: Wash the Prophet (ﷺ) while his clothes are on him. So they stood round the Prophet (ﷺ) and washed him
Grade: Hasan

Hadith #3142 - Sunan Abi Dawud - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Umm Atiyyah Ansariyah; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came in when his daughter died, and he said: Wash her with water and lotus leaves three or five times or more than that if you think fit, and put camphor, or some camphor in the last washing, then inform me when you finish. When we had finished we informed him, and he threw us his lower garment saying: Put it next to her body. Malik’s version has: that is, his lower garment (izar); and Musaddad did not say: He entered in.
Grade: Sahih

Hadith #3143 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Hafsa bint Sirin حفصة بنت سيرين; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
We braided her hair in three plaits.
Grade: Sahih

Hadith #3144 - Sunan Abi Dawud - Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Hafsa bint Sirin حفصة بنت سيرين; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
we braided her hair in three plaits and placed them behind her back, one plait of the front side and the two side plaits.
Grade: Sahih

Hadith #3166 - Sunan Abi Dawud - Ayoub al-Sakhtiyani أيوب السختياني; Hafsa bint Sirin حفصة بنت سيرين; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
The Prophet (ﷺ) said: If any Muslim dies and three rows of Muslims pray over him, it will assure him (of Paradise). When Malik considered those who accompanied a bier to be a few, he divided them into three rows in accordance with this tradition.
Grade: Da'if

Hadith #5269 - Sunan Abi Dawud - Abd al-Whab bin Abd عبد الوهاب بن عبد الرحيم; Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Muhammad bin Hsan محمد بن حسان; Sulaiman bin 'Abdur Rahman سليمان بن عبد الرحمن بن عيسى; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
When a physician consulted the Prophet (ﷺ) about putting frogs in medicine, he forbade him to kill them.
Grade: Sahih